HUBUNGAN DESAIN KERJA DAN DISIPLIN DENGAN PRODUKTIVITAS PEGAWAI DIREKTORAT JENDERAL PENDIDIKAN NONFORMAL DAN INFORMAL - IFRAN KARIM (Jurnal Manajemen Pendidikan, 2011)
This research aims to determine the relationship: (1) job design with productivity; (2) discipline with productivity; and (3) the relation between job design and discipline with productivity.The research method using survey by correlation approach. This research used as a sample of 80 employees, and 20 employees for testing, and selected based on a simple random technique (simple random sampling). The study was conducted at Directorate General of Non-formal and Informal Education.Technique data collecting was using the instrument in the form of questionnaire. This instrument is calibrated with the test item validity and reliability coefficients. To test the validity of using Pearson Product Moment correlation, while the reliability coefficient is calculated using the formula of Cronbach Alpha. The results showed that: first, there were positive relationship between job design with productivity; secondly, there is a positive relationship between discipline with productivity; thirdly, there is a positive relationship between job design and discipline together with employees productivity. The implication of this research is an effort in improving the productivity of employees can be done through job design and discipline.